A scuffing model considering additive depletion in boundary lubrication. Issue 3 (13th November 2019) - Lee, Bora; Yu, Yonghun; Cho, Yong-Joo
Abstract : Purpose: This paper aims to propose a new scuffing model caused by the depletion of additives in boundary lubrication condition. Design/methodology/approach: The differential equation governing the distribution of additive content in the fluid film was used. This formula was derived from the principle of mass conservation of additives considering the consumption due to surface adsorption of wear particles. The occurrence of scuffing was determined by comparing the wear rate of the oxide layer with the oxidation rate. Findings: If the additive becomes depleted while sliding, the scuffing failure occurs even at a low-temperature condition below the critical temperature. The critical sliding distance at which scuffing failure occurred was suggested. The experimental data of the existing literature and the theoretical prediction using the proposed model are shown to be in good agreement. Originality/value: It is expected to be used in the design of oil supply grooves for sliding bearings operating under extreme conditions or in selecting the minimum initial additive concentration required to avoid scuffing failure under given contact conditions.